Moderately differentiated neuroendocrine carcinoma of the larynx: A clinicopathologic study of 54 cases - Bruce M. Wenig; Vincent J. Hyams; Dennis K. Heffner (1988)
Fifty-four cases of primary laryngeal moderately differentiated neuroendocrine carcinoma from the Armed Forces Institute of Pathology Otolaryngic Tumor Registry (AFIP-OTR) are reported. The tumors most often present in men in their sixth and seventh decades of life and are heralded by an array of symptoms, the most frequent being hoarseness. The primary site was most often the supraglottic larynx. The investigation has included light-microscopic, histochemical, immunocytochemical, and electron microscopic analyses which support expression of both neuroendocrine and epithelial differentiation. Conservative surgery alone can be utilized if early identification of the tumor and complete surgical removal are assured. The follow-up of the patients reveals 62% as remaining tumor-free after surgical extirpation over periods ranging from 1 month to 16 years (median: 3 years, 9 months). Factors adversely affecting prognosis include metastatic disease at initial presentation, incomplete surgical removal, and vascular or lymphatic invasion. There was no correlation between tumor size, morphologic pattern, mitoses or necrosis, and survival. Sixty-eight percent of the patients gave a history of long-term cigarette smoking. The classification and pathogenesis of these neoplasms remains the focus of much speculation. They are suggested as arising from the cells of the dispersed neuroendocrine system (DNES). However, a more uniform and descriptive nomenclature is necessary. This study resolves this and other issues along with a presentation of clinicopathologic data of the tumor entity.